Ethanolysis of rapeseed oil - Distribution of ethyl esters, glycerides and glycerol between ester and glycerol phases - Hájek, Martin; Černoch, Michal; Skopal, František (Elsevier, 2010)
The distribution of ethyl esters, triglycerides, diglycerides, monoglycerides and glycerol between the ester and glycerol phase was investigated after the ethanolysis of rapeseed oil at various reaction conditions. The determination of these substances in the ester and glycerol phases was carried out by the GC method. The amount of ethyl esters in the glycerol phase was unexpectedly high and therefore the possibility of the reduction of this amount was investigated. The distribution coefficients and the weight distributions of each investigated substance were calculated and compared mutually. The distribution coefficients between the ester and glycerol phase increase in this sequence: glycerol, monoglycerides, diglycerides, ethyl esters and triglycerides. Soaps and monoglycerides in the reaction mixture cause a worse separation of ethyl esters from the reaction mixture. The existence of a non-separable reaction mixture was observed also, and its composition was determined.
Keywords: Biodiesel; Transesterification; ethanolysis; separation; distribution